2015
DOI: 10.1589/jpts.27.1645
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and analgesic effects of low-level laser therapy on the postoperative healing process

Abstract: [Purpose] This study aimed to evaluate the anti-inflammatory and analgesic effects of intraoral application of low-level laser therapy (660 nm) to control pain, swelling and interincisal opening following the extraction of mandibular third molars. [Subjects and Methods] Ten patients underwent removal of lower third molars using the same surgical protocol and pharmacological approach. In the postoperative period, all patients received four consecutive daily sessions of low-level laser therapy, beginning 24 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…In all these studies, the third molar was the extracted tooth except in one study conducted on premolar's extraction sockets. 23 PBM effectively reduced post extraction pain as shown in 16 studies 5,6,13,[15][16][17][18][19][24][25][26][27][28][29][30][31] compared with placebo. In these studies, wavelengths ranged from 650 to 980 nm.…”
Section: Study Selectionmentioning
confidence: 78%
See 1 more Smart Citation
“…In all these studies, the third molar was the extracted tooth except in one study conducted on premolar's extraction sockets. 23 PBM effectively reduced post extraction pain as shown in 16 studies 5,6,13,[15][16][17][18][19][24][25][26][27][28][29][30][31] compared with placebo. In these studies, wavelengths ranged from 650 to 980 nm.…”
Section: Study Selectionmentioning
confidence: 78%
“…11,12 A number of studies have demonstrated that PBM has an impact on the management of pain and swelling. 5,[13][14][15][16][17][18] Ferrante reported that PBM is useful for pain reduction after impacted third molar surgery. 19 In an animal study, it has been shown that PBM could reduce pain intensity, inflammation, and immunological reactions; while in human studies some factors including the type of disease, surgery, and laserrelated variables influence the outcome of PBM.…”
Section: Introductionmentioning
confidence: 99%
“…Low-power laser irradiation has been proposed as a treatment (lowlevel laser therapy; LLLT) to harness the stimulatory effect of light on living tissues. LLLT using a visible light laser with a wavelength of 400-700 nm reportedly promotes wound healing [9,10] and cell proliferation [11,12], relieves pain [13][14][15][16][17], and induces bone formation [18][19][20]. Several reports have indicated that LLLT is suitable for use in orthodontic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported less postoperative pain and discomfort and also reduction in use of analgesics and local anesthetic drugs in laser surgery. [16][17][18] However, there are still some disadvantages in regard to adjunctive laser treatment in orthodontics. Application of laser is limited due to the high cost of laser devices.…”
Section: Introductionmentioning
confidence: 99%